Prediction of Flap Necrosis by Using Indocyanine Green Videoangiography in Cases of Venous Occlusion in the Epigastric Flap Model of the Rat - Ritschl, Lucas M.; Schmidt, Leonard H.; Fichter, Andreas M.; Hapfelmeier, Alexander; Kanatas, Anastasios; Wolff, Klaus-Dietrich; Mücke, Thomas (Journal of Reconstructive Microsurgery Open, 2018)
Background A compromised free flap perfusion attributable to vascular occlusion requires immediate operative correction. Indocyanine green (ICG) videoangiography may reduce the risk of partial skin flap necrosis in high-risk free flaps in patients undergoing head and neck reconstruction. The purpose of this study was to determine the role of ICG in cases of venous congestion in a rat model.Methods A standardized epigastric flap was raised and repositioned in 35 rats. Full venous occlusion of the draining superficial inferior epigastric vein was temporarily applied for 4, 5, 6, or 7 hours. Blood flow measurements including simultaneous laser-Doppler flowmetry and tissue spectrophotometry (oxygen-to-see [O2C]) and ICG videoangiography with the FLOW 800 tool were performed before flap raising, after temporary venous stasis, and after clinical monitoring for 1 week. The Youden index computed from the receiver operating characteristic curve was used to define an optimal cutoff value for necrosis prediction after 4 and 6 hours of stasis.Results The ICG videoangiography with the FLOW 800 tool was found to be superior to O2C in the prediction of flap necrosis. The accuracy of prediction was moderate after an interval of 4 hours of stasis (area under the curve [AUC] = 0.661; 95% confidence interval [CI]: 0.489–0.834) and good after 6 hours of stasis (AUC = 0.787; 95% CI: 0.65–0.915).Conclusions The O2C does not reliably predict tissue necrosis in cases of venous congestion. ICG videoangiography is a valuable tool that can predict clinical outcome and provide guidance on whether to salvage a congested flap.
Keywords: venous congestion; indocyanine green videoangiography; prediction of flap necrosis